A photocatalyst modified with copper-doped carbon quantum dots and its preparation method and application

The photocatalyst modified by copper-doped carbon quantum dots is combined with the g-C3N4/BiOBr heterojunction system, and the superdisulfate is activated by light to carry out advanced oxidation reaction, solving the problem of difficult degradation of tetracycline antibiotics in water, achieving efficient removal of tetracycline antibiotics, and significantly improving the biochemical properties of the water.

CN119034783BActive Publication Date: 2025-04-15DALIAN NATIONALITIES UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411165866.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-04-15
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently degrade tetracycline antibiotics in water, making it difficult to solve environmental pollution.

Method used

A photocatalyst modified with copper-doped carbon quantum dots was used to combine with the g-C3N4/BiOBr heterojunction system, and the perdisulfate was activated by light to carry out advanced oxidation reactions to remove tetracycline antibiotics in water.

Benefits of technology

The removal efficiency of more than 90% of tetracycline antibiotics has been achieved, and the biochemical properties of the water body have been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119034783B_ABST
    Figure CN119034783B_ABST
Patent Text Reader

Abstract

The present invention provides a copper-doped carbon quantum dot modified photocatalyst and its preparation method and application, belonging to the technical field of photocatalyst preparation. The preparation method comprises the following steps: after corn stalks and copper salts are uniformly mixed in water, a hydrothermal reaction is carried out, and then the obtained reaction solution is centrifuged to collect the upper suspension and the lower filter residue respectively; the upper suspension is filtered, and then the filtered filtrate is dialyzed I to obtain a Cu-doped carbon quantum dot solution; after the lower filter residue is dispersed in a sodium hydroxide solution, H2O2 is added to react I, and then the obtained reaction solution is dialyzed II to obtain a hydrochar Cu-doped carbon quantum dot solution; BiOBr and a carbon quantum dot solution are added to a dispersion containing g-C3N4 to react II to obtain the copper-doped carbon quantum dot modified photocatalyst. The photocatalyst of the present invention can efficiently activate peroxydisulfate to degrade organic pollutants in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalyst preparation, and in particular to a copper-doped carbon quantum dot-modified photocatalyst and a preparation method and application thereof. Background Art

[0002] Antibiotics are widely used in therapeutic processes and animal husbandry. However, neither humans nor animals can completely metabolize these antibiotics, resulting in their direct excretion into the environment as parent compounds. Due to high hydrophilicity and low volatility, antibiotics show significant persistence in the environment, which leads to disturbances in natural water environments. Among various antibiotics, the application of tetracycline antibiotics has received widespread attention, such as tetracycline (TC) and oxytetracycline (OTC). As ubiquitous substances in nature, tetracycline antibiotics are difficult to be completely degraded by traditional water treatment processes. Therefore, it is imperative to develop efficient and green water pollution control technologies to improve the biodegradability of tetracycline antibiotic wastewater. Summary of the invention

[0003] Based on the above content, the purpose of the present invention is to provide a copper-doped carbon quantum dot modified photocatalyst and its preparation method and application. The copper-doped carbon quantum dot modified photocatalyst provided by the present invention can efficiently activate peroxydisulfate to degrade organic pollutants in water.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] One of the technical solutions of the present invention is a method for preparing a photocatalyst modified with copper-doped carbon quantum dots, comprising the following steps:

[0006] The corn stalks and copper salt are mixed evenly in water and subjected to hydrothermal reaction, and then the obtained reaction solution is centrifuged to collect the upper suspension and the lower residue respectively;

[0007] Filtering the upper suspension, and then dialyzing the filtrate obtained by filtration I to obtain a Cu-doped carbon quantum dot solution;

[0008] After dispersing the lower layer of filter residue in a sodium hydroxide solution, H2O2 is added to carry out reaction I, and then the obtained reaction solution is dialyzed II to obtain a hydrochar Cu-doped carbon quantum dot solution;

[0009] BiOBr and carbon quantum dot solution are added to the dispersion containing g-C3N4 to carry out reaction II to obtain the copper-doped carbon quantum dot modified photocatalyst; the carbon quantum dot solution is the Cu-doped carbon quantum dot solution or the hydrochar Cu-doped carbon quantum dot solution.

[0010] The second technical solution of the present invention is a photocatalyst modified with copper-doped carbon quantum dots prepared by the above preparation method.

[0011] The third technical solution of the present invention is the use of the above-mentioned copper-doped carbon quantum dot-modified photocatalyst in activating peroxydisulfate to degrade organic pollutants in water.

[0012] The present invention discloses the following technical effects:

[0013] From the perspective of environmental friendliness and improving the carrier transfer rate at the heterojunction interface, the present invention prepares carbon quantum dots (CQDs) from waste biomass corn stalks, successfully introduces Cu-doped CQDs into a Z-type heterojunction photocatalyst (g-C3N4 / BiOBr) system, and uses photocatalyst-assisted activation of peroxydisulfate (PDS) to perform advanced oxidation reactions under light conditions to remove typical tetracycline antibiotics from water. The removal efficiency of tetracycline antibiotics reaches more than 90% (within 40 minutes). BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 This is the XRD spectrum of the photocatalyst prepared in Example 1.

[0016] Figure 2 This is the FT-IR spectrum of the photocatalyst prepared in Example 1.

[0017] Figure 3 The efficiency of the photocatalyst prepared in Example 1 in degrading OTC in the PDS / light system (a), the pseudo-first-order kinetics of the reaction system (b), and the removal rate of various pollutants by Cu-CD / BOV / ECN in the PDS / light system (c).

[0018] Figure 4 are the different influencing factors of the degradation system on the degradation efficiency of OTC, where (a) is the dosage of Cu-CD / BOV / ECN, (b) is the PDS concentration, and (c) is the initial concentration of OTC; the reaction conditions are: [catalyst] = 20 mg (except (a)), [PDS] = 1 mM (except (b)), [OTC] = 20 mg / L (except (c)), T = 25°C.

[0019] Figure 5 Different factors affecting the degradation efficiency of OTC in the water environment system, where (a) is HA, (b) is water temperature, (c) is PE, (d) is anion, and (e) is different water matrices. DETAILED DESCRIPTION

[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0021] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0022] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0023] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0024] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0025] Bismuth oxybromide (BiOBr) is known for its high chemical stability and tunable band structure, and is an excellent candidate for constructing heterojunction composite materials with g-C3N4. The present invention combines the exfoliated g-C3N4 with BiOBr, and the difference in work function can promote the preferential combination of electrons in BiOBr and photogenerated holes in g-C3N4, further forming a heterojunction. This heterojunction structure can significantly improve the transfer of photogenerated carriers and enhance their redox ability.

[0026] Carbon quantum dots (CQDs) are effective electron transfer intermediates due to their low toxicity, high chemical stability, photogenerated electron transfer, and excellent upconversion luminescence ability. CQDs can also be used as photosensitizers to enhance the ability to capture light, thereby broadening the response range of composite photocatalysts in visible light. Copper doping in carbon quantum dots can enhance the internal electric field of the heterojunction, promote carrier migration, and reduce the recombination of carriers during the migration process.

[0027] From the perspective of environmental friendliness and improving the carrier transfer rate at the heterojunction interface, the present invention prepares carbon quantum dots (CQDs) from waste biomass corn stalks, successfully introduces Cu-doped CQDs into a Z-type heterojunction photocatalyst (g-C3N4 / BiOBr) system, and uses photocatalyst-assisted activation of peroxydisulfate (PDS) to carry out advanced oxidation reactions under light conditions to remove typical tetracycline antibiotics in water.

[0028] Based on the above content, the present invention provides a method for preparing a photocatalyst modified with copper-doped carbon quantum dots, comprising the following steps:

[0029] The corn stalks and copper salt are mixed evenly in water and subjected to hydrothermal reaction, and then the obtained reaction solution is centrifuged to collect the upper suspension and the lower residue respectively;

[0030] The upper suspension is filtered, and the filtrate is dialyzed I to obtain a Cu-doped carbon quantum dot solution (denoted as Cu-CD);

[0031] After dispersing the lower filter residue (i.e., hydrochar) in a sodium hydroxide solution, H2O2 is added to perform reaction I, and then the obtained reaction solution is dialyzed II to obtain a hydrochar Cu-doped carbon quantum dot solution (referred to as Cu-HCD);

[0032] BiOBr and a carbon quantum dot solution are added to a dispersion containing g-C3N4 to carry out reaction II, thereby obtaining the copper-doped carbon quantum dot-modified photocatalyst; the carbon quantum dot solution is the Cu-doped carbon quantum dot solution or the hydrochar Cu-doped carbon quantum dot solution. When the carbon quantum dot solution is the Cu-doped carbon quantum dot solution, the obtained copper-doped carbon quantum dot-modified photocatalyst is recorded as Cu-CD / BOV / ECN; when the carbon quantum dot solution is the hydrochar Cu-doped carbon quantum dot solution, the obtained copper-doped carbon quantum dot-modified photocatalyst is recorded as Cu-HCD / BOV / ECN.

[0033] In some embodiments of the present invention, the present invention first dries and grinds the corn stalks to prepare corn stalk powder.

[0034] In some embodiments of the present invention, the copper salt is copper chloride dihydrate; the mass volume ratio of the corn straw, copper chloride dihydrate and water is (3-6) g: (0.8525-2.5575) g: (80-180) mL, preferably 4 g: 1.705 g: 80 mL.

[0035] The reason why the copper salt selected in the present invention is copper chloride dihydrate is that copper chloride dihydrate is widely used as the preferred copper source for copper doping due to its excellent water solubility, moderate reactivity and mild reaction conditions. It is easy to disperse evenly, convenient to accurately control the doping concentration, and the by-products are easy to handle and will not have a significant impact on the purity of the material. In contrast, other copper salts such as copper sulfate and copper nitrate have poor solubility or reactivity, may generate insoluble or harmful by-products, and are difficult to achieve uniform doping, thereby affecting the structure and performance of the material.

[0036] The reason why the present invention selects corn stalks as biomass materials is that replacing corn stalks with other biomass materials will affect the structure, optical properties, yield and surface chemical properties of carbon quantum dots when preparing carbon quantum dots. Corn stalks, as a raw material for carbon quantum dots, have a high carbon content, good structural properties and a high yield, and can generate carbon quantum dots with uniform structure and excellent optical properties. In addition, corn stalks are widely available, low cost, and have environmental advantages. However, different biomass materials have different organic components and pyrolysis characteristics, which may cause carbon quantum dots to differ in composition, luminescence characteristics and functional group distribution, thereby affecting their performance in specific applications.

[0037] In the present invention, the ratio of corn stalks to copper chloride dihydrate may have the following effects on the properties and performance of carbon quantum dots:

[0038] (1) Copper doping efficiency

[0039] If the amount of corn stalks increases and the proportion of copper chloride dihydrate decreases, the efficiency of copper doping may decrease. Insufficient doping of copper ions may cause the conductivity, optical properties or catalytic activity of carbon quantum dots to decrease, and undoped carbon quantum dots may exhibit properties similar to pure carbon quantum dots. If the amount of copper chloride dihydrate increases and the proportion of corn stalks decreases, it may cause excessive copper ions to fail to be uniformly doped into carbon quantum dots, forming uneven doping or causing copper aggregation, which may produce by-products or undesirable copper nanoparticles, affecting the purity and performance of carbon quantum dots.

[0040] (2) Structure and morphology of carbon quantum dots

[0041] More corn stalks will produce more carbon quantum dots, but the copper doping concentration is reduced, which may lead to larger carbon quantum dots or a morphology closer to undoped carbon quantum dots, affecting their conductivity and other physical and chemical properties. Higher copper content may affect the morphology of carbon quantum dots, resulting in irregular morphology or the presence of a large number of undesirable copper phases (such as copper oxide or copper chloride particles), thus affecting the uniformity and functionality of the material.

[0042] (3) Optical and electrochemical properties

[0043] A low copper content may not significantly change the optical and electrochemical properties of carbon quantum dots, and the carbon quantum dots may maintain properties similar to pure carbon quantum dots, reducing the enhancement effect of copper doping on the target performance. Excessive copper content may cause changes in the luminescence characteristics of carbon quantum dots, may introduce new luminescence centers or change their emission spectra, and the electrochemical activity may increase, but excessive copper may cause agglomeration or affect the stability of the material.

[0044] (4) Yield and stability

[0045] A higher corn straw ratio may increase the overall yield of carbon quantum dots, but the copper content of doping is reduced, resulting in low doping efficiency, which may require further optimization or post-treatment to achieve the desired performance. A lower corn straw ratio may reduce the overall yield of carbon quantum dots, and excessive copper may induce unstable reactions or by-products, affecting the stability and application performance of the final material.

[0046] In some embodiments of the present invention, the method for uniformly mixing corn stalks and copper salt in water can be any mixing method well known to those skilled in the art, such as stirring, and the stirring time is preferably 60 minutes.

[0047] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 200° C. and the time is 4 hours.

[0048] In the present invention, when preparing carbon quantum dots, the temperature and time of the hydrothermal reaction have a significant effect on the performance of the final product. If the reaction temperature is higher than 200°C, the degree of carbonization of the carbon quantum dots will increase, which may cause the particles to be too large and the optical properties to decrease. At the same time, the surface functional groups will decrease, affecting the water solubility and chemical activity. When the temperature is lower than 200°C, the carbonization reaction is insufficient, and larger, disordered carbon quantum dots with weaker fluorescence intensity but more surface functional groups may be produced. If the reaction time exceeds 4 hours, the carbon quantum dots may be over-carbonized, resulting in attenuation of optical properties and changes in surface chemical properties; if the time is less than 4 hours, the carbon quantum dots may be insufficiently carbonized, the structure may be uneven, and the fluorescence efficiency may be reduced.

[0049] In some embodiments of the present invention, the filter membrane used to filter the upper suspension is a 0.22 μm filter membrane; the dialysis I is: dialysis in a 1000-1500D dialysis bag for 24 hours. After dialysis I, the concentration of the Cu-doped carbon quantum dot solution is about 2 g / L.

[0050] In some embodiments of the present invention, the mass volume ratio of the lower layer filter residue, the sodium hydroxide solution and H2O2 is 0.1g:50mL:2mL; and the concentration of the sodium hydroxide solution is 0.3mol / L.

[0051] In the present invention, if the proportion of the lower layer residue is too high, there may be too much solid matter in the reaction system, which increases the difficulty of the reaction, poor dispersion of the carbon quantum dots, and the product may form agglomerates, affecting its optical properties. Insufficient residue may lead to insufficient carbon source, reduced carbon quantum dot yield, and substandard optical and physical properties.

[0052] Excessive sodium hydroxide will cause an overly alkaline environment, resulting in incomplete carbonization of the filter residue, and the generated carbon quantum dots are larger in size and irregular in structure. Insufficient alkalinity may lead to low reaction efficiency and incomplete carbonization. The product may contain incompletely carbonized organic matter, affecting the fluorescence intensity and stability of the carbon quantum dots.

[0053] Excessive H2O2 may lead to excessive oxidation reaction, destroy the structure of carbon quantum dots, reduce the fluorescence intensity, and may produce uneven particles. Insufficient oxidant may lead to insufficient oxidation of carbon quantum dots and incomplete formation of surface functional groups, affecting the dispersion and optical properties of carbon quantum dots.

[0054] In some embodiments of the present invention, reaction I is carried out by stirring at room temperature; the stirring reaction time is 8 hours.

[0055] In the present invention, extending the stirring time may further promote the uniform distribution and interaction of the two materials, which is beneficial to improving the uniformity of the composite material. However, if the time is too long, the material may be redistributed, or even cause local aggregation, which reduces the uniformity. Long-term stirring may strengthen the electrostatic interaction between the two materials and increase the interfacial bonding force. However, too long stirring time may also cause the weakly bound areas on the interface to dissociate, which weakens the overall bonding strength. And long-term stirring may cause the material to experience excessive mechanical stress in the solution, which may cause partial degradation or damage of the structure, affecting the stability and functionality of the composite material.

[0056] If the stirring time is too short, insufficient stirring time may result in the two materials not being fully mixed, leading to the inhomogeneity of the composite material, forming local enrichment or voids, and affecting the overall performance of the material. In addition, a shorter stirring time may not be able to fully form a stable electrostatic interaction, resulting in a weaker bonding force between the two materials, thereby affecting the mechanical properties and stability of the composite material. Although a shorter stirring time can reduce mechanical damage to the material, if the mixing is not sufficient, it may lead to an incomplete structure of the composite material and affect the photocatalytic performance.

[0057] In some embodiments of the present invention, after the reaction I is completed, the step of adjusting the pH of the obtained reaction solution to 5-9 is also included; the reagent used to adjust the pH of the reaction solution is HCl solution.

[0058] In some embodiments of the present invention, the dialysis time of the dialysis II is 3-5 days. After dialysis II, the concentration of the obtained hydrochar Cu-doped carbon quantum dot solution is about 2 g / L.

[0059] The dialysis time for Cu-doped carbon quantum dots on hydrochar should be as long as 3-5 days. Sufficient time can usually effectively remove small molecule impurities and obtain a purer carbon quantum dot solution. This length of time can ensure the uniformity and stability of the carbon quantum dots. If the time is too short, the impurities may not be completely removed, resulting in low purity of the carbon quantum dots, which may affect its optical properties and stability. If the time is too long, there will generally be no negative impact, but exceeding the necessary time may not significantly improve the purity, and will increase operating costs and time. For dialyzed carbon quantum dots, 3-5 days of dialysis time can usually effectively remove impurities and ensure high purity and performance. Depending on the specific situation, the dialysis time may need to be adjusted to achieve the best results.

[0060] In some embodiments of the present invention, the mass volume ratio of the g-C3N4, BiOBr, and carbon quantum dot solution is 500 mg: 500 mg: 10 mL.

[0061] In the present invention, the ratio of g-C3N4, BiOBr and carbon quantum dot solution will have the following effects:

[0062] (1) The proportion of g-C3N4 is too high or too low:

[0063] Too high a proportion of g-C3N4 may lead to excessive coverage of g-C3N4 in the photocatalyst, reduce the effective contact area between BiOBr and carbon quantum dots, reduce the separation efficiency of photogenerated electron-hole pairs, and thus weaken the photocatalytic performance. Too low a proportion of g-C3N4 may lead to its insufficient role in the composite material, unable to effectively participate in the transfer of photogenerated electrons, and affect the overall photocatalytic efficiency.

[0064] (2) BiOBr ratio is too high or too low:

[0065] Too high a proportion of BiOBr may lead to an uneven structure of the composite material, weaken the composite effect of carbon quantum dots and g-C3N4, and affect the light absorption performance and catalytic activity of the material. Too low a proportion of BiOBr may not effectively play its role as a photocatalytic active center, weaken the activity of the photocatalyst under visible light, and reduce the efficiency of pollutant degradation.

[0066] (3) The proportion of carbon quantum dot solution is too high or too low:

[0067] Too high a ratio of carbon quantum dot solution may lead to over-modification, affecting the structural uniformity of the photocatalyst, causing particle agglomeration, hindering light absorption and electron transfer, and thus reducing the photocatalytic efficiency. Too low a ratio of carbon quantum dot solution may lead to insufficient surface modification, failing to significantly improve the electron-hole separation efficiency and surface activity of the photocatalyst, and affecting the overall performance of the photocatalyst.

[0068] In some embodiments of the present invention, the preparation method of the g-C3N4 is: calcining melamine at 550°C for 4 hours, then cooling to room temperature, grinding, calcining at 550°C for 4 hours, cooling to room temperature, and grinding to obtain the g-C3N4 (denoted as ECN).

[0069] In some embodiments of the present invention, the preparation method of the BiOBr is as follows: bismuth nitrate pentahydrate and potassium bromide (KBr) are added to a mixed solution (50 ml of ethylene glycol (EG) + 10 ml of deionized water), and the mixture is stirred to obtain solution I; polyvinyl pyrrolidone (PVP) is dissolved in ethylene glycol, and ultrasonicated to obtain a PVP solution; the PVP solution is added dropwise to the solution I, and after stirring, the resulting mixture is reacted at 160° C. for 6 hours to obtain the BiOBr (denoted as BOV).

[0070] In some embodiments of the present invention, the molar volume ratio of the mixed solution, bismuth nitrate pentahydrate, potassium bromide, polyvinyl pyrrolidone and ethylene glycol is 60mL:2mmol:4mmol:3mmol:10mL; the ultrasonic time is 30min, and the purpose of ultrasonic treatment for 30 minutes is to ensure that PVP is fully dissolved and uniformly dispersed in ethylene glycol, and to provide a uniform and bubble-free solution system for subsequent mixing and reaction.

[0071] In some embodiments of the present invention, the preparation method of the dispersion containing g-C3N4 is: dispersing g-C3N4 in a mixed solvent with a volume ratio of water to ethanol of 1:1; the mass volume ratio of the g-C3N4 and the mixed solvent is 500 mg:40 mL.

[0072] In some embodiments of the present invention, the reaction II is carried out by stirring at room temperature; the stirring reaction time is 8 hours.

[0073] In the present invention, extending the stirring time may further promote the uniform distribution and interaction of the two materials, which is beneficial to improving the uniformity of the composite material. However, if the time is too long, the material may be redistributed, or even cause local aggregation, which reduces the uniformity. Long-term stirring may strengthen the electrostatic interaction between the two materials and increase the interfacial bonding force. However, too long stirring time may also cause the weakly bound areas on the interface to dissociate, which weakens the overall bonding strength. And long-term stirring may cause the material to experience excessive mechanical stress in the solution, which may cause partial degradation or damage of the structure, affecting the stability and functionality of the composite material.

[0074] If the stirring time is too short, insufficient stirring time may result in the two materials not being fully mixed, leading to the inhomogeneity of the composite material, forming local enrichment or voids, and affecting the overall performance of the material. In addition, a shorter stirring time may not be able to fully form a stable electrostatic interaction, resulting in a weaker bonding force between the two materials, thereby affecting the mechanical properties and stability of the composite material. Although a shorter stirring time can reduce mechanical damage to the material, if the mixing is not sufficient, it may lead to an incomplete structure of the composite material and affect the photocatalytic performance.

[0075] In some embodiments of the present invention, after the reaction II is completed, the steps of centrifugation, washing and drying are also included.

[0076] The present invention also provides a copper-doped carbon quantum dot-modified photocatalyst prepared by the preparation method described in the above technical solution.

[0077] The present invention also provides the use of the copper-doped carbon quantum dot-modified photocatalyst described in the above technical solution in activating peroxydisulfate to degrade organic pollutants in water.

[0078] In some embodiments of the present invention, the organic pollutant is tetracycline (TC), oxytetracycline (OTC), rhodamine B (RhB), methylene blue (MB) or norfloxacin (NFX).

[0079] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0080] Chemicals and materials: Melamine (C3H6N6, 99.5%) was provided by China Traditional Chinese Medicine Chemical Reagent Co., Ltd. Bismuth nitrate pentahydrate (Bi(NO3)3·5H2O, 99.0%), ascorbic acid (VC, 99.7%), and disodium hydrogen phosphate (NaH2PO4·H2O, 99.5%) were obtained from Tianjin Kemei Chemical Reagent Co., Ltd. Potassium bromide (KBr, 99.0%) was purchased from Tianjin Damao Chemical Reagent Co., Ltd. All chemicals used in the present invention were analytically pure and no further purification was required.

[0081] The preparation method of g-C3N4 in the embodiment is: 10g of melamine is placed in a muffle furnace and calcined at 550°C for 4h, then cooled to room temperature, ground, placed in a muffle furnace again and calcined at 550°C for 4h, cooled to room temperature, and ground to obtain the g-C3N4 (denoted as ECN).

[0082] The preparation method of BiOBr is as follows: 2mmol bismuth nitrate pentahydrate and 4mmol potassium bromide are added to a mixed solution (50ml ethylene glycol (EG) + 10ml deionized water), stirred for 30min to obtain solution I, 3mmol polyvinyl pyrrolidone (PVP) is dissolved in 10ml EG, and ultrasonically treated for 30min to obtain a PVP solution; the obtained PVP solution is added dropwise to solution I, stirred for 1h, and then the obtained mixture is transferred to a high-temperature reactor and heated at 160°C for 6h to obtain BiOBr (denoted as BOV).

[0083] Example 1

[0084] This embodiment provides a copper-doped carbon quantum dot modified photocatalyst, the preparation steps are as follows:

[0085] Step 1. Pour 4.00 g corn stalk powder and 1.705 g copper chloride dihydrate into 80 mL deionized water, stir for 60 min, mix evenly, react at 200 ° C in a stainless steel autoclave for 4 h, then centrifuge the resulting reaction solution to collect the upper suspension and the lower filter residue respectively;

[0086] Step 2. Filter the upper suspension using a 0.2 μm filter membrane, and then dialyze the filtrate in a 1000-1500D dialysis bag for 24 hours to obtain a Cu-doped carbon quantum dot solution (referred to as Cu-CD);

[0087] Step 3. After dispersing 0.1 g of the lower layer filter residue (i.e., hydrochar) in 50 mL of 0.3 mol / L sodium hydroxide solution, 2 mL of H2O2 was added and stirred at room temperature for 8 h to obtain a golden brown transparent liquid, and the pH was adjusted to 6 with HCl solution, followed by dialysis for 5 days to obtain a hydrochar Cu-doped carbon quantum dot solution (denoted as Cu-HCD);

[0088] Step 4. Disperse 500 mg of ECN into 40 mL of mixed solvent (V 水 :V 乙醇 =1:1), then 500 mg BOV and 10 mL Cu-CD were added in sequence, stirred at room temperature for 8 h, then centrifuged, washed, and dried in sequence to obtain a Cu-doped carbon quantum dot modified photocatalyst (denoted as Cu-CD / BOV / ECN);

[0089] Disperse 500 mg ECN into 40 mL of mixed solvent (V 水 :V 乙醇 =1:1), then 500 mg BOV and 10 mL Cu-HCD were added in sequence, stirred at room temperature for 8 h, then centrifuged, washed, and dried in sequence to obtain a hydrochar Cu-doped carbon quantum dot modified photocatalyst (denoted as Cu-HCD / BOV / ECN);

[0090] Disperse 500 mg ECN into 50 mL of mixed solvent (V 水 :V 乙醇 =3:2), and then 500 mg BOV was added. The mixture was stirred at room temperature for 8 hours, and then centrifuged, washed, and dried to obtain a photocatalyst (referred to as BOV / ECN).

[0091] Effect verification:

[0092] 1. Characterization: The crystal structure of the photocatalyst was determined by X-ray diffractometer (XRD, Shimadzu XRD-6000). Fourier transform infrared spectrometer (FT-IR, Shimadzu IR Prestige-21) was used to characterize the photocatalyst at 400-4000 cm -1 The surface functional groups of photocatalysts were analyzed in this study.

[0093] Sample characterization results: Figure 1The XRD patterns of the samples prepared in Example 1 are shown. In the XRD pattern of ECN, the (002) crystal plane formed at 27.7° due to the π-π interlayer stacking of the heptazine unit can be clearly observed. The XRD spectrum of BOV shows that it has a tetragonal phase (JCPDS No.09-0393). The XRD patterns of BOV / ECN, Cu-HCD / BOV / ECN and Cu-CD / BOV / ECN all show diffraction peaks of ECN and BOV, but no obvious carbon quantum dot (CQD) diffraction peaks are observed in the XRD pattern of the composite material, which may be due to the small amount of CQD introduced and the disordered structure. The XRD pattern shows that the composite material provided by the present invention is mainly composed of ECN and BOV coexisting. Although the introduction of CQD has no significant effect on the crystal structure of BOV / ECN, it changes its crystallinity. Among them, the crystal structure of Cu-CD / BOV / ECN is the best, especially in the (110) crystal plane. The high crystallinity suggests that Cu-CD / BOV / ECN may have higher catalytic activity.

[0094] The molecular structure of the prepared photocatalyst was analyzed by infrared spectroscopy ( Figure 2 ). In BOV, it is clearly observed that the -1 The absorption peak of Bi-O bond is 1298 cm -1 and 1657cm -1 It comes from the OH bending vibration and the stretching vibration of the Bi-Bi bond. In ECN, it can be clearly observed at 806cm -1 The triazine structure at 3010~3300cm -1 The peaks are from the stretching vibration of water molecules adsorbed on the surface, -NH2 or OH, 1200~1650cm -1 The peaks are mainly derived from the stretching vibrations of aromatic CN heterocycles and C=N, among which 1240 cm -1 ,1331cm -1 ,1418cm -1 ,1574cm -1 CN stretching vibration, 1641cm -1 It is the stretching vibration of C=N. The characteristic peaks of BOV and ECN can be clearly observed in the infrared spectrum of the composite material, and the addition of the two carbon quantum dots does not cause the change of the molecular structure of the composite material.

[0095] 2. Photocatalytic experiment

[0096] 50mL of OTC solution (20mg / L) was added to a beaker, followed by 30mg of photocatalyst. The mixture was stirred for 10 minutes using a magnetic stirrer under dark conditions and then ultrasonicated for 20 minutes to ensure that the photocatalyst was evenly distributed in the OTC solution and to establish adsorption-desorption equilibrium. Photocatalytic experiments were performed by irradiating the reaction solution with a 300W xenon lamp simulating sunlight, and 1mmol of PDS solution was added before turning on the light. The reaction solution was taken out at given time intervals, filtered through a 0.22μm filter, and the absorbance at 357nm was measured using a UV-visible spectrophotometer. The degradation of pollutants during the photocatalytic process follows a pseudo-first-order kinetic model (Formula (1)):

[0097] ln(C t / C0)=-kt (1)

[0098] Where C0 is the initial pollutant concentration, C t is the pollutant concentration at time t, and k is the reaction rate constant.

[0099] 2.1 Analysis of the performance of activated peroxydisulfate (PDS) in degrading oxytetracycline (OTC)

[0100] Figure 3 The catalytic activities of all samples in the PDS / light irradiation system are shown. Figure 3 (a) shows that when only PDS is added, the removal rate of OTC is only 9.6%. The catalyst with carbon quantum dots showed better efficiency in degrading OTC than ECN (70.3%), BOV (60.1%) and BOV / ECN (89.7%) under the PDS / light system. Among them, Cu-CD / BOV / ECN showed the highest degradation efficiency of 98.2% within 40 minutes, which was significantly higher than Cu-HCD / BOV / ECN (91.2%). Figure 3 (b) also shows that Cu-CD / BOV / ECN has the highest rate constant (0.0985min) in the PDS / light system. -1 ). The results show that the addition of Cu-CD can achieve better performance in degrading OTC than that of Cu-HCD. Figure 3 (c) (reaction conditions: [catalyst] = 20 mg, [PDS] = 1 mM, [pollutant] = 20 mg / L, T = 25°C) shows the degradation performance of Cu-CD / BOV / ECN in the PDS / light system for various organic pollutants. The removal rates of RhB and MB can reach 100% within 10 min and 20 min, and the removal rate of NFX can reach 80% within 40 min.

[0101] 2.2 Different factors affecting the degradation efficiency of OTC by degradation system

[0102] from Figure 4 As can be seen in (a), when the dosage of Cu-CD / BOV / ECN increased from 10 mg to 30 mg, the removal rate of OTC increased from 83.3% to 98.2%, which indicates that with the increase of the amount of catalyst, there are more active centers, which helps to improve the degradation efficiency. When the dosage of Cu-CD / BOV / ECN increased from 30 mg to 50 mg, the removal rate of OTC remained at around 98%, indicating that further increasing the dosage of the catalyst alone cannot significantly improve the catalytic efficiency. Therefore, a photocatalyst dosage of 30 mg was selected for subsequent experiments. Figure 4 (b) shows the degradation curve of OTC in the reaction system with different dosages of PDS. The OTC removal efficiency of the Cu-CD / BOV / ECN+PDS / light system continues to increase as the PDS concentration increases from 0.2mM to 1mM. The oxidation activity of the Cu-CD / BOV / ECN+PDS / light system reaches a peak at a PDS concentration of 1mM, indicating that a higher concentration of PDS can provide more free radicals for the photocatalytic reaction. On the contrary, when the PDS concentration (1.5mM) is too high, it will have a negative impact on the photocatalytic reaction, resulting in a decrease in the degradation performance of OTC. This is because at a fixed catalyst dosage, an increase in PDS concentration will lead to self-cleaning between free radicals. Figure 4 (c) shows the effect of initial OTC concentration on the degradation system. As the initial OTC concentration increases, the degradation efficiency of the degradation system for OTC gradually decreases. When the initial OTC concentration is 30 mg / L and 40 mg / L, the removal rate of OTC is only 80.2% and 76.2%. This is because the higher the initial OTC concentration, the higher the concentration of intermediate products, resulting in increased competitive consumption between OTC molecules and their by-products. On the other hand, at a higher OTC concentration, the active sites on the catalyst surface can be covered, limiting the generation of free radicals.

[0103] like Figure 5 As shown in (a), when the concentration of humic acid (HA) increases to 10 mg / L, the OTC removal efficiency of the Cu-CD / BOV / ECN+PDS / light system drops to 89.8%. This is because HA can absorb ultraviolet and visible light, resulting in a decrease in the light energy received by the photocatalyst. On the other hand, HA can react with free radicals (such as ·OH and ·SO4) generated by photocatalysis. ·- ) reaction, quenching these active species. Figure 5 (b) shows the effect of temperature on the removal of OTC by the Cu-CD / BOV / ECN+PDS / light system. When the temperature increased from 20°C to 40°C, the removal rate of OTC increased from 89.6% to 99.5%, indicating that high reaction temperature accelerated the decomposition of PDS and formed more active species for OTC degradation.

[0104] Since microplastics (PE) are commonly found in polluted water and may affect the performance of photocatalysts, the present invention also investigates the effect of microplastics on the Cu-CD / BOV / ECN+PDS / light system. Figure 5 As shown in (c), when the PE content gradually increases, the efficiency of Cu-CD / BOV / ECN+PDS / light system for OTC decreases from 98.2% to 88.1%. This may be because PE particles cover the active sites on the surface of the photocatalyst, hindering the contact with the OTC molecules and affecting the reaction efficiency.

[0105] Considering that various inorganic anions present in actual water bodies may have an impact on the catalytic reaction, the present invention also explores the effects of various inorganic anions on the removal performance of OTC. - 、SO4 2- 、HPO4 2- and HCO3 - Effect of (10mM) on OTC removal in Cu-CD / BOV / ECN+PDS / light system ( Figure 5 (d)). Cl - and SO4 2- The inhibition of OTC removal is due to Cl - The reaction between free radicals (·OH and SO4·-) (Eqs. (1)-(3)), and excess SO4 2- It will have a negative impact on the decomposition of PDS. HPO4 2- The inhibitory effect on OTC oxidation is due to HPO4 2- Will react with OH and SO4 2- Quenching occurs (Eqs.4). HCO3 - It is an effective scavenger of ·OH and SO4·-, producing a much weaker oxidant CO3·-, resulting in a decrease in degradation efficiency (Eqs. 5, 6).

[0106] Cl - +SO4 ·- →SO4 2- +Cl · (1)

[0107] Cl - + ·OH→ClHO ·- (2)

[0108] Cl - +Cl · →Cl2 ·- (3)

[0109] HPO4 2- +SO4 ·- →HPO4- +SO4 2- (4)

[0110] HCO3 – +SO4 ·– →SO4 2– +CO3 ·– +H + (5)

[0111] HCO3 – + ·OH→CO3 ·– +H2O (6)

[0112] Deionized water, tap water, lake water and sea water were selected to evaluate the OTC degradation potential in real water bodies under the Cu-CD / BOV / ECN+PDS / light system ( Figure 5 (e)). The experimental results show that within 40 min, the degradation rate of the Cu-CD / BOV / ECN+PDS / light system in tap water (88.1%), lake water (81.7%) and seawater (78.2%) decreased, which may be due to the presence of various ions and other organic pollutants in actual water bodies, which consume the active free radicals in the system. In general, the Cu-CD / BOV / ECN+PDS / light system has great potential for practical environmental remediation.

[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of a copper-doped carbon quantum dot modified photocatalyst in activating peroxydisulfate to degrade organic pollutants in water, characterized in that: The method for preparing the copper-doped carbon quantum dot modified photocatalyst comprises the following steps: The corn stalks and copper salt are mixed evenly in water and subjected to hydrothermal reaction, and then the obtained reaction solution is centrifuged to collect the upper suspension and the lower residue respectively; Filtering the upper suspension, and then dialyzing the filtrate obtained by filtration I to obtain a Cu-doped carbon quantum dot solution; After dispersing the lower layer of filter residue in a sodium hydroxide solution, H2O2 is added to carry out reaction I, and then the obtained reaction solution is dialyzed II to obtain a hydrochar Cu-doped carbon quantum dot solution; Adding BiOBr and a carbon quantum dot solution to a dispersion containing g-C3N4 to carry out reaction II to obtain the copper-doped carbon quantum dot-modified photocatalyst; the carbon quantum dot solution is the Cu-doped carbon quantum dot solution or the hydrochar Cu-doped carbon quantum dot solution; The mass volume ratio of the lower layer filter residue, sodium hydroxide solution and H2O2 is 0.1g:50mL:2mL; the concentration of the sodium hydroxide solution is 0.3mol / L; Reaction I is carried out by stirring at room temperature; the stirring reaction time is 8 hours.

2. The use of the copper-doped carbon quantum dot modified photocatalyst according to claim 1 in activating peroxydisulfate to degrade organic pollutants in water, characterized in that: The copper salt is copper chloride dihydrate; the mass volume ratio of the corn stalks, copper chloride dihydrate and water is (3-6) g: (0.8525-2.5575) g: (80-180) mL.

3. The use of the copper-doped carbon quantum dot modified photocatalyst according to claim 1 in activating peroxydisulfate to degrade organic pollutants in water, characterized in that: The temperature of the hydrothermal reaction is 200° C. and the time is 4 hours.

4. The use of the copper-doped carbon quantum dot modified photocatalyst according to claim 1 in activating peroxydisulfate to degrade organic pollutants in water, characterized in that: The filter membrane used to filter the upper suspension is a 0.22 μm filter membrane; the dialysis I is: dialysis in a 1000-1500D dialysis bag for 24 hours.

5. The use of the copper-doped carbon quantum dot modified photocatalyst according to claim 1 in activating peroxydisulfate to degrade organic pollutants in water, characterized in that: The mass volume ratio of the g-C3N4, BiOBr and carbon quantum dot solution is 500 mg:500 mg:10 mL.

6. The use of the copper-doped carbon quantum dot modified photocatalyst according to claim 1 in activating peroxodisulfate to degrade organic pollutants in water, characterized in that: The reaction II is carried out by stirring at room temperature; the stirring reaction time is 8 hours.

Citation Information

Patent Citations

  • Preparation method and application of copper-doped CQD (carbon quantum dot) / bismuth tungstate composite photocatalyst

    CN108786787A

  • Tetracycline degradation method

    CN111204837A

  • G-C3N4 nanosheet composite catalyst as well as preparation method and application thereof

    CN118356961A